Individual risk factors and the mother-child relationship in borderline personality disorder traits in children and adolescents - Fleck, Leonie (2022)
Borderline personality disorder (BPD) is a severe mental disorder characterized by pervasive patterns of instability of affect, self-image, and relationships. For a long time, BPD has been predominantly studied in adults, given the notion that personality in youth is still subject to changes. Research of the past decades has shown that the diagnosis of BPD is equally reliable and valid in adolescence. BPD has been started to be approached from a life span perspective that acknowledges that both adaptive and maladaptive personality traits can express and change throughout the life span. Developmental models of BPD assume an interplay of maladaptive family and parenting factors and an intrapersonal temperamental disposition to experience intense emotion. The interplay of caregiving behavior and child vulnerability is supposed to lead to insufficient co-regulation throughout the life span, impeding the development of child social communication and self-regulatory abilities. These developmental pathways have however not extensively been operationalized in youth. Lastly, research on the expression of symptoms during childhood age is rare, limiting our understanding of the early stages of the developing disorder. The aim of the current work is to extend knowledge about the interplay of intrapersonal and mother-child-relationship risk factors, explore physiological co-regulation in the context of BPD pathology, and to expand the life span perspective on BPD pathology to primary school age. Article 1 applied a 14-year longitudinal design to study how postpartum maternal bonding impairment (MBI) as an indicator of very early mother-child relationship difficulties interacts with child temperament. MBI and low harm avoidance were risk factors for BPD traits and overall personality dysfunction. Interaction effects indicated that children low in harm avoidance and high in novelty seeking were more vulnerable to the effects of MBI, as they developed higher levels of overall personality dysfunction. Regarding BPD specifically, girls were more susceptible to the effect of MBI than boys. Article 2 investigated the process of physiological co-regulation during mother-child interaction. The hypothalamic–pituitary–adrenal (HPA) axis shows dysregulation among BPD patients. The current work therefore studied physiological co-regulation of the HPA axis, indexed by mother-child cortisol synchrony. Patterns of cortisol synchrony varied as a function of child BPD pathology and dyadic behavior. Article 3 aimed at gathering knowledge about differences and similarities of BPD traits during middle childhood and adolescence. BPD trait frequencies did not significantly differ between children and adolescents. BPD traits were associated with impairments such as higher comorbidity and lower quality of life in both age groups. However, age-related differences emerged indicating more strained mother-child relationships in adolescents compared to children with BPD traits.
Keywords: Hochschulschrift